2018
DOI: 10.1002/jcp.27770
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA NEAT1 accelerates the proliferation and fibrosis in diabetic nephropathy through activating Akt/mTOR signaling pathway

Abstract: Accumulating evidence has indicated the significant roles of long noncoding RNAs (lncRNAs) in the pathophysiology of diabetic nephropathy (DN). LncRNA nuclear enriched abundant transcript 1 (NEAT1) has been reported to exert a key role in the progression of several diseases including diabetes. However, the role of NEAT1 in the regulation of DP progression remains barely known. Therefore, our study aimed to investigate the role of NEAT1 in a streptozotocin‐induced diabetes model (DM) of rats and glucose‐induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 29 publications
5
62
0
Order By: Relevance
“…Several lncRNAs, such as MALAT1 and KCNQ1OT1, and miRNAs, such as miR-214–3p, miR-23c, and miR-22–3p, have been identified to be involved in the cell pyroptosis mechanism in diabetes-related nephropathy, cardiomyopathy, and atherosclerosis [36-38]. Consistent with our observations, NEAT1 was significantly increased in STZ-induced DN rat models and HG-induced rat mesangial cells; the function of NEAT1 in DN was proposed to promote fibrogenesis [13, 14]. On the other hand, NEAT1 has been demonstrated to enhance activation of inflammasomes and subsequent caspase-1-dependent pyroptosis and reduce inflammatory responses in mouse macrophages [15].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Several lncRNAs, such as MALAT1 and KCNQ1OT1, and miRNAs, such as miR-214–3p, miR-23c, and miR-22–3p, have been identified to be involved in the cell pyroptosis mechanism in diabetes-related nephropathy, cardiomyopathy, and atherosclerosis [36-38]. Consistent with our observations, NEAT1 was significantly increased in STZ-induced DN rat models and HG-induced rat mesangial cells; the function of NEAT1 in DN was proposed to promote fibrogenesis [13, 14]. On the other hand, NEAT1 has been demonstrated to enhance activation of inflammasomes and subsequent caspase-1-dependent pyroptosis and reduce inflammatory responses in mouse macrophages [15].…”
Section: Discussionsupporting
confidence: 84%
“…lncRNA-NR_033515 promoted mesangial cell proliferation and increased the expression of proliferation-related and fibrogenesis-related genes by regulating miR-743b-5p expression in DN patients [12]. Most recent studies also suggested that lncRNA-Neat1 (NEAT1) exerted a key role in DN, demonstrating that the expression of NEAT1 was upregulated in both in vivo and in vitro models of DN [13]. A further study also demonstrated that NEAT1 accelerated proliferation and EMT, contributing to fibrogenesis in DN [14].…”
Section: Introductionmentioning
confidence: 99%
“…The knockdown of PVT-1 expression significantly caused the reduction of these molecules (Alvarez and DiStefano, 2011). Another reported lncRNA is the Nuclear Enriched Abundant Transcript-1 (NEAT1), which is also highly expressed due to hyperglycemia, and NEAT1 interacts with AKT/mTOR pathway (Huang et al, 2019). Inhibition of NEAT1 expression in an animal model of DN causes a reduction of TGFB1, FN, and COL4A1 production (Huang et al, 2019).…”
Section: Long Noncoding Rnas In Renal Hypertrophy and Ecm Accumulationmentioning
confidence: 99%
“…Another reported lncRNA is the Nuclear Enriched Abundant Transcript-1 (NEAT1), which is also highly expressed due to hyperglycemia, and NEAT1 interacts with AKT/mTOR pathway (Huang et al, 2019). Inhibition of NEAT1 expression in an animal model of DN causes a reduction of TGFB1, FN, and COL4A1 production (Huang et al, 2019). Similarly, lncRNA ERBB4-IR also promotes renal fibrosis via the activation of the TGFB/SMAD3 pathway (Zhou et al, 2014;Sun et al, 2018b).…”
Section: Long Noncoding Rnas In Renal Hypertrophy and Ecm Accumulationmentioning
confidence: 99%
“…Numerous studies collectively indicated the importance of intricate crosstalk existing between lncRNAs and PI3K/AKT/mTOR signaling [27,28]. mTOR frequently exerts as an oncogenic signaling cascade in human malignancies [29].…”
Section: Discussionmentioning
confidence: 99%